Cloning, expression and purification of the complete domain of the η-carbonic anhydrase from Plasmodium falciparum. (4th November 2016) - Del Prete, Sonia; De Luca, Viviana; De Simone, Giuseppina; Supuran, Claudiu T.; Capasso, Clemente
Abstract: The antimalarial drugs are of fundamental importance in the control of malaria, especially for the lack of efficient treatments and acquired resistance to the existing drugs. For this reason, there is a continuous work in identifying novel, less toxic and effective chemotherapies as well as new therapeutic targets against the causative agents of malaria. In this context, a superfamily of metalloenzymes named carbonic anhydrases (CAs, EC 4.2.1.1) has aroused a great interest as druggable enzymes to limit the development of Plasmodium falciparum gametocytes. CAs catalyze a common reaction in all life domains, the carbon dioxide hydration to bicarbonate and protons (CO2 + H2 O ⇔ HCO3 - + H + ). P. falciparum synthesizes pyrimidines de novo starting from HCO3 -, which is generated from CO2 through the action of the η-CA identified in the genome of the protozoan. Here, we propose a procedure for the preparation of a wider portion of the protozoan η-CA, named PfCAdom (358 amino acid residues), with respect to the truncated form prepared by Krungkrai et al. (PfCA1, 235 amino acid residues). The results evidenced that the recombinant PfCAdom, produced as a His-tag fusion protein, was 2.7 times more active with respect the truncated form PfCA1.